Indigenous knowledge and traditional management of cashew (Anacardium occidentale L.) genetic resources in Benin. - CHABI-SIKA, KAMIROU; ADOUKONOU, AWO SAGBADJA HUBERT; AHOTON, ESSÈHOU LÉONARD; ADEBO, I.; ADIGOUN, F.A.; SAIDOU, ALIOU; KOTCHONI, SIMEON; AHANCHEDE, ADAM; BABA-MOUSSA, LAMINE SAÏD (My University, 2013)
In order to evaluate producers’ knowledge level on cashew tree production and its socio-cultural importance, present an ethnobotanical study has been conducted from January to March 2013 in three ecological zones of Benin. A total of 347 cashew producers of seven ethnic groups have been interviewed from 21 villages. Data were collected by using participatory research approach through group discussions followed by individual investigations. The results of this study showed that farmers have very good knowledge about the fructification, the length of the flowering period, the different varieties grown and their level of productivity through time. Traditionally, many varieties are recognized and diverse criteria such as the color, the form and the shape of the apple, the form and the shape of the nut were used by the producers for the identification and the description of the cashew varieties. Besides the shape of the nut and the plant productivity are the two main selection criteria of cashew varieties for the installment of their plantations. On the other hand, the leaf, the bark and the roots are used in the traditional medicine for the treatment of some diseases. Cashew is the second important cash crop after cotton in the study area because of its contribution to the income of the producers. These findings are important for the management and exploitation of cashew genetic resources for a better production in Benin.
Keywords: Cashew; Ethnobotany; Genetic diversity; Plantation management; Benin